2014
DOI: 10.1532/hsf98.2014317
|View full text |Cite
|
Sign up to set email alerts
|

Extended Vertical Transseptal Approach versus Transseptal Approach for Mitral Valve Operation

Abstract: The extended vertical transseptal approach not only affords excellent exposure of the mitral valve, but also is safe for maintaining sinus node function compared with the transseptal approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, postoperative pleural effusion was detected more significantly among the trans-septal group than those in left atriotomy group. Similarly, there was no increased risk of permanent pacemaker insertion after TS, in addition to the majority of arrhythmias are transient, in accordance to some research (14,21) . While, in their multivariate study, Lukac et al found that the TS method was an independent risk factor for pacemaker insertion (hazard ratio [HR]: 2.2, 95% confidence level).CI: 1.2-4.1; p = 0.014 (22) .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, postoperative pleural effusion was detected more significantly among the trans-septal group than those in left atriotomy group. Similarly, there was no increased risk of permanent pacemaker insertion after TS, in addition to the majority of arrhythmias are transient, in accordance to some research (14,21) . While, in their multivariate study, Lukac et al found that the TS method was an independent risk factor for pacemaker insertion (hazard ratio [HR]: 2.2, 95% confidence level).CI: 1.2-4.1; p = 0.014 (22) .…”
Section: Discussionsupporting
confidence: 90%
“…Perhaps the differences between our results and those reported by the Nienaber and Glower [32] study are due to the shorter atrial incision, faster atrial closure time, and lesser injury to the sinus nodal artery in the mini-TS approach. Wang et al [33] concluded that the extending vertical transseptal approach affords excellent exposure of the mitral valve.…”
Section: Left Ventricular Outflow Tract [Lvot] Obstruction May Occur After Redo Surgical Mitral Valve Replacement [Smvr]mentioning
confidence: 99%
“…15 Emerging minimally invasive approaches may eventually supplant the traditional atriotomy or transseptal approaches that are currently widely used for MV surgeries. 16 Reports of the frequency of postoperative arrhythmias in cohorts of patients undergoing these procedures, compared to patients who underwent more invasive traditional procedures, will shed light on the relationship between MV approach and the creation of electrophysiological substrates.…”
Section: Voltage Mappingmentioning
confidence: 99%